Systematic review of 3D facial expression recognition methods. (April 2020) - Alexandre, Gilderlane Ribeiro; Soares, José Marques; Pereira Thé, George André
Highlights: Recognition rates for Fear and Sadness expressions still remain a challenge. A trend towards keypoint-independent methods has been observed. There is a preference for local scope regions of interest for face representation. Significant information on preprocessing techniques have been neglected. The diversity of the experimentation setups limits the fair comparison among studies. Abstract: The three-dimensional representation of the human face has emerged as a viable and effective way to characterize the facial surface for expression classification purposes. The rapid progress in the area continually demands its up-to-date characterization to guide and support research decisions, specially for newcomer researchers. This systematic literature review focus on investigating three major aspects of 3D facial expression recognition methods: face representation, preprocessing and classification experiments. The investigation of 49 specialized studies revealed the preferential types of data and regions of interest for face representation in recent years, as well as a trend towards keypoint-independent methods. In addition, it brings to light current weaknesses regarding the report of preprocessing techniques and identifies challenges concerning the current possibility of fair comparison among multiple methods. The presented findings outline essential research decisions whose the regardful report is of great value to this research community.